Toxicity and efficacy of 6-thioguanine versus 6-mercaptopurine in childhood lymphoblastic leukaemia: a randomised trial. - Vora, A; Mitchell, C; Lennard, L; Eden, T; Kinsey, SE; Lilleyman, J; Richards, S (2006)
BACKGROUND: 6-mercaptopurine has been a standard component of long-term continuing treatment for childhood lymphoblastic leukaemia, whereas 6-thioguanine has been mainly used for intensification courses. Since preliminary data have shown that 6-thioguanine is more effective than 6-mercaptopurine, we compared the efficacy and toxicity of the two drugs for childhood lymphoblastic leukaemia. METHODS: Consecutive children with lymphoblastic leukaemia diagnosed in the UK and Ireland between April, 1997, and June, 2002, were randomly assigned either 6-thioguanine (750 patients) or 6-mercaptopurine (748 patients) during interim maintenance and continuing therapy. All patients received 6-thioguanine during intensification courses. We analysed event-free and overall survival on an intention-to-treat basis. We obtained toxicity data using an adverse-event reporting system, with follow-up questionnaires to seek detailed information for specific toxicities. This trial is registered with the International Standard Randomised Controlled Number 26727615 with the name ALL97. FINDINGS: After a median follow up of 6 years, there was no difference in event-free or overall survival between the two treatment groups. Although 6-thioguanine conferred a significantly lower risk of isolated CNS relapse than did 6-mercaptopurine (odds ratio [OR] 0.53, 95% CI 0.30-0.92, p=0.02), the benefit was offset by an increased risk of death in remission (2.22, 1.20-4.14, p=0.01), mainly due to infections during continuing therapy. Additionally, 95 patients developed veno-occlusive disease of the liver. Of these, 82 were randomly assigned 6-thioguanine, representing 11% of all 6-thioguanine recipients. On long-term follow-up, about 5% of 6-thioguanine recipients have evidence of non-cirrhotic portal hypertension due to periportal liver fibrosis or nodular regenerative hyperplasia. INTERPRETATION: Compared with 6-mercaptopurine, 6-thioguanine causes excess toxicity without an overall benefit. 6-mercaptopurine should remain the thiopurine of choice for continuing therapy of childhood lymphoblastic leukaemia.